Solar irradiance measurement instrumentation and power solar generation forecasting based on Artificial Neural Networks (ANN): A review of five years research trend - Pazikadin A.R.; Rifai D.; Ali K.; Malik M.Z.; Abdalla A.N.; Faraj M.A. (Elsevier B.V., 2023)
Electric power system control; Electric power transmission networks; Forecasting; Hybrid systems; Information management; Instrument errors; Neural networks; Photovoltaic cells; Solar concentrators; Solar energy; Solar radiation; Forecasting accuracy; Irradiance; Photovoltaic; Renewable energy source; Solar; Solar irradiance measurement; Solar photovoltaic plants; Solar photovoltaic power generations; Solar power generation; accuracy assessment; artificial neural network; calibration; design; forecasting method; instrumentation; power generation; solar power; solar radiation; article; artificial neural network; calibration; forecasting; human; Scopus; weather; Scopus